Contract for difference from the Islamic finance perspective / Nur Syazana Mohd Nasir, Azlyantiny Mohammad and Norafiza Mohd Hardi - Mohd Nasir, Nur Syazana; Mohammad, Azlyantiny; Mohd Hardi, Norafiza (Universiti Teknologi MARA, Kedah, 2022)
The high unemployment rate in Malaysia (DOSM, 2021) during the COVID-19 event has forced individuals to seek alternative ways of making money. One of the examples includes online financial trading, which is conducted through synthetic brokerage located inside or outside of Malaysia, mainly through offshore financial institutions (Griffith, 2010). Online financial trading brokerage, regulated or unregulated, offers a myriad of financial assets and derivatives to trade such as foreign exchange currency (FOREX), crypto-currency, precious metal, energy, Crude Palm Oil (CPO), Brent, stocks, index, etc. Financial transactions of these assets and derivatives are performed using contracts, mostly via a Contract for Difference (CFD) (Mitchell, 2021). The popularity of online CFD trading in Malaysia has soared as it offers large profits (or losses) to individuals using small capital (CFI, 2022). This phenomenon is also boosted and promoted by brokerage through Introductory Broker (IB) (Finance Feeds, 2022) and the emergence of e-teaching by YouTube’s content creators. The major features of CFD that accelerate its acceptance in Malaysia include, but are not limited to the following: (1) individuals trade without actually owning or taking physical delivery of the underlying asset, thus having access to the asset at a lower cost rather than buying the asset completely; (2) the trading time is available to Malaysians as the brokerage operates 24 hours, 5 days per week; (3) short-term holding is permissible and the process of starting and ending the contract is easier electronically; (4) the use of small margin and higher leverage compared to the stock market; (5) the use of dollar currency, which multiplies the profit (or loss) from the transaction (Mitchell, 2021). The CFD mechanism behind the brokerage is not disclosed publicly and the term can only be found if an individual scrutinizes the brokerage website. Therefore, since most brokerage customers in Malaysia are Muslims, the need to discuss the contract in simpler terms from the Islamic finance perspective is disregarding the view of the law and regulations of the country. In general, CFD works as a legally binding contract between two parties, namely the buyer and the seller, stipulating that the buyer will pay to the seller the difference between the current value of an asset and its value at contract closure time, wherein the opposite likewise applies (Norman, 2009). This definition of CFD contradicts both the Futures contract (Cliffe, n.d) and the Option contract (Foot, n.d) in the sense that CFD does not expire. In this regard, since CFD is traded using the value of the asset, the contract can be initiated by paying a small premium or margin to the quantity of the lot to be traded (Chen, 2020).